Language Change on Social Media - Celine Christina Luhulima; Endar Rachmawaty Linuwih; Duncan Reinhart Hutagaol; Nofiyanti Nofiyanti (ITScience (Information Technology and Science), 2024)
Language change is the permanent alteration of a language's features and usage over time, affecting various aspects such as sound, vocabulary, meaning, and syntax. This research explores language change in the context of social media, specifically focusing on YouTube podcasts. The main goal is to understand how certain parts of speech, like pronouns, verbs, and adjectives, transform into specialized terms unique to the social media environment. The study aims to answer the question: